2011
DOI: 10.3390/en4050826
|View full text |Cite
|
Sign up to set email alerts
|

Affects of Mechanical Milling and Metal Oxide Additives on Sorption Kinetics of 1:1 LiNH2/MgH2 Mixture

Abstract: Abstract:The destabilized complex hydride system composed of LiNH 2 :MgH 2 (1:1 molar ratio) is one of the leading candidates of hydrogen storage with a reversible hydrogen storage capacity of 8.1 wt%. A low sorption enthalpy of ~32 kJ/mole H 2 was first predicted by Alapati et al. utilizing first principle density function theory (DFT) calculations and has been subsequently confirmed empirically by Lu et al. through differential thermal analysis (DTA). This enthalpy suggests that favorable sorption kinetics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…As shown in Table 1, the quantity of MgO in cycled samples is about 46%. This finding suggests that oxidation arises from both, high-temperature reaction with oxygen impurities physisorbed on the samples during handling [6,7] and from the reactions: MgH2→Mg+H2 2Mg+VO2→ 2MgO + V An increase of MgO quantity due to reaction with vanadium oxides has been already reported by several authors [20,21]. The interaction of V with H2 may lead to formation of an interstitial solid solution, of VH~0.8, or of VH2 depending on the operating temperature and pressures At the conditions of our H-sorption cycles, an interstitial solid solution of H in bcc V is expected according to V-H thermodynamics [5].…”
Section: Results and Disscusionsupporting
confidence: 63%
“…As shown in Table 1, the quantity of MgO in cycled samples is about 46%. This finding suggests that oxidation arises from both, high-temperature reaction with oxygen impurities physisorbed on the samples during handling [6,7] and from the reactions: MgH2→Mg+H2 2Mg+VO2→ 2MgO + V An increase of MgO quantity due to reaction with vanadium oxides has been already reported by several authors [20,21]. The interaction of V with H2 may lead to formation of an interstitial solid solution, of VH~0.8, or of VH2 depending on the operating temperature and pressures At the conditions of our H-sorption cycles, an interstitial solid solution of H in bcc V is expected according to V-H thermodynamics [5].…”
Section: Results and Disscusionsupporting
confidence: 63%
“…Moreover, considerable efforts have been devoted to improving the hydrogen storage performance of the LiNH 2 -MgH 2 system by doping with various additives, such as metal oxides and transition metal halides. 13,14 Anton et al reported that the addition of Fe 2 O 3 and V 2 O 5 signicantly reduced the amount of ammonia emission during the initial decomposition. 13 Price et al systematically investigated the effects of different transition metal halides (TiCl 3 , VCl 3 , ScCl 3 , and NiCl 2 ) on the sorption properties of a 1 : 1 molar ratio of LiNH 2 to MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The lower enthalpy value of this system suggests near ambient temperature desorption, however, it can occur only at more than 150 • C practically, which must be caused by the kinetic constraints. Thus, in order to improve the sorption kinetics, several additives were attempted with this system [318][319][320][321][322][323][324][325][326]. Shahi et al [319] studied the effect of various V-based additives and found VCl 3 as the best catalyst among them.…”
Section: Catalysts For Amidesmentioning
confidence: 99%